2022
DOI: 10.3389/fmicb.2022.918774
|View full text |Cite
|
Sign up to set email alerts
|

Screening and evaluation of lactic acid bacteria with probiotic potential from local Holstein raw milk

Abstract: There are massive bacteria in the raw milk, especially the lactic acid bacteria (LABs), which have been considered probiotics in humans and animals for a long time. Novel probiotics are still urgently needed because of the rapid development of the probiotic industry. To obtain new LABs with high probiotic potential, we obtained 26 LAB isolates, named L1 ~ L26, from local Holstein raw milk collected from a farm whose milk had never been used for LAB isolation. We identified them at the species level by biochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 45 publications
2
14
1
Order By: Relevance
“…These results are desirable properties of potential probiotics that could enhance bacterial growth and promote the recovery of gut microbiota. [ 51 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are desirable properties of potential probiotics that could enhance bacterial growth and promote the recovery of gut microbiota. [ 51 ]…”
Section: Discussionmentioning
confidence: 99%
“…These results are desirable properties of potential probiotics that could enhance bacterial growth and promote the recovery of gut microbiota. [51] Oxidative stress is a defense mechanism for the host against invading pathogens. [48] The results of this experiment indicated that the mutant strain ΔaldB and the WT strain have similar tolerance to H 2 O 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…catalase activity, cell motility) were performed using standard protocols [54]. Furthermore, a haemolysis test on blood agar plates was carried out as previously described [55][56][57].…”
Section: Phenotypic Characterizationmentioning
confidence: 99%
“…Thus, the application and exploitation of functional LAB strains in the food fermentation industry, livestock industry and other related industries has greatly increased over the years (De Melo Pereira et al, 2018). However, more studies have emerged that focus on the rational improvement of industrially useful LAB strains (Zhang et al, 2022). Therefore, more precise confirmation of the phenotypes of novel LAB strains will certainly be required before their adoption for better application purposes.…”
Section: Introductionmentioning
confidence: 99%